PEMBENTUKAN KARAKTER KEWIRAUSAHAAN PADA GEN Z - Rian, Hesti; Gustiawan, Handa; Darmawan, Darmawan (POLITEKNIK LP3I JAKARTA, 2025)
The formation of entrepreneurial character in Generation Z is important to prepare them to face future challenges and contribute to the economy. Generation Z has unique characteristics that can be utilized to develop an entrepreneurial spirit, such as technological knowledge, creativity, and concern for social issues. With an entrepreneurial spirit, Generation Z can create their own jobs, reduce dependence on formal employment, and make a positive contribution to the economy. Generation Z has a high concern for social and environmental issues. These values ​​can be the basis for running a sustainable and responsible business. The Lecturer Team conducted community service activities to educate Generation Z about entrepreneurship.